2015
DOI: 10.5897/jmpr2015.5746
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloid constitution of Nerium oleander using gas chromatography-mass spectroscopy (GC-MS)

Abstract: Oleander is an evergreen shrub or small tree from 5 to 25-ft tall containing gummy sticky sap in the dogbane family Apocynaceae. In this study, the alkaloid compounds of Nerium oleander (NO) have been evaluated. The chemical compositions of the leaf ethanol extract of N. oleander were investigated using gas chromatography-mass specroscopy (GC-MS). GC-MS analysis of N. oleander alkaloid leaf ethanol extract revealed the existence of the 5-hydrooxy methylfurfural, β-d-allopyranoside, methyle 6dioxy-2-o methyl, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 18 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Whatman No.1 filter paper was used to separate the extract of plant. The filtrates were used for further phytochemical analysis (Imad et al, 2015a). It was again filtered through sodium sulphate in order to remove the traces of moisture.…”
Section: Preparation Of Samplementioning
confidence: 99%
“…Whatman No.1 filter paper was used to separate the extract of plant. The filtrates were used for further phytochemical analysis (Imad et al, 2015a). It was again filtered through sodium sulphate in order to remove the traces of moisture.…”
Section: Preparation Of Samplementioning
confidence: 99%
“…(Figures 4 to 22). M. viridis was found to be more active at lower concentration against all the pathogenic bacterial strains and these results could be due to differences in chemical composition of the oils (Oumzil et al, 2002;Zenasni et al, 2008;Imad et al, 2015). The earlier report on the essential oil of M. viridis from Tunisie revealed the presence of carvone, 1,8-cineole, and limonene (Mkaddem et al, 2009), while the study from Morocco showed that the oil contains high pulegone content (Talbaoui et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The tests were carried out in triplicate. The antifungal activity was evaluated by measuring the inhibition-zone diameter observed after 48 h of incubation (Huda et al, 2015;Ameera et al, 2015).…”
Section: Determination Of Antifungal Activitymentioning
confidence: 99%
“…The seeds have medical uses and traditionally applied for curing digestive disorder, pain in joints and rheumatism. Stomachic, spasmolytic, carminative, diarrhoea and dyspepsia of various origin's coriander are also used in aromatherapy (Gil et al, 2002;Eikani et al, 2007;Grosso et al, 2008Imad et al, 2015). It is used to treat female diseases such as menoxenia, ovulation type dysfunctional uterine bleeding (Paarakh, 2009).…”
Section: Introductionmentioning
confidence: 99%